Simulation approach in Matlab/Simulink for the main components of a positioning unit in a closed-loop hydraulic circuit - Wolf , Benjamin (2016)
The replacement of on-off solenoids with solenoids which can adjust the spool position of a directional valve proportionally to their input voltage was the groundwork for the development of proportional valve technology. Due to their robustness and well-priced properties, proportional valves are a good alternative to conventional servo-solenoid valves. Indeed, servosolenoid valves are highly precise but that makes them highly expensive as well. Additionally, they place great demands on maintenance and industrial surroundings. Hence proportional valves are widely-used in automation engineering. A common application is the positioning of actuators. Thus, a closed-loop circuit is necessary. In doing so, the proportional valve’s input voltage is the manipulated value which enables a certain area for the oil to pass through the valve. Therefore, the flow rate to the actuator can be changed to control the actuator position with high precision. In this thesis the main components of a hydraulic positioning unit shall be modelled and simulated using the software Matlab/Simulink. That includes the actuator, the pressure relief valve, connecting pipes and of course the proportional directional control valve. With this model the positioning unit can be tested under different conditions to make predictions on how the system is going to react. Due to the fact that it was not possible to collect measured data from the several components, measured data from the datasheets have been used to verify the models. For the actuator was no datasheet available. Consequently, only a general model could be created. The dynamic behavior of the pressure relief valve could be obtained by using the dimensions given in the datasheet. However, the datasheet does not provide any curves related to dynamic behavior. Therefore, only the static behavior was verifiable. The simulation of the proportional directional control valve was divided into a static and a dynamic part. Based on flow, pressure and leakage curves given by the manufacturer, pseudo-section functions have been created. These functions characterize the relationship between normalized spool position and flow rate. For simulating the dynamic behavior, a nonlinear Simulink model was created. The model was fitted to nonlinear frequency response data points by using a Nelder-Mead simplex optimization algorithm. Methodologies and models were subsequently tested with used data from the manufacturer. The good quality of the results seems to support the approach. Nevertheless, the Simulink model has to be adjusted more properly to the measurement curves. All important components of a hydraulic positioning unit have been modelled. It is recommended to make further improvements to adjust the Simulink model more properly to the given curves in the datasheet. Subsequently, all components can be connected together to implement the closed-loop circuit.